RESPON PENGGUNAAN BERBAGAI BAHAN AKTIVATOR PADA AKTIVASI PARTENOGENESIS OOSIT KAMBING HASIL IVM - Kholifah Holil, Eva Ari Wahyuni, Hari Soepriandono Gatot Ciptadi (SAINSTIS, 2011)
Parthenogenetic activation is one method that can be used to determine the quality of IVM oocytes results before further use to other reproductive technologies (IVF and transfer core). In parthenogenetic activation can be used various activators such as ethanol, Ca Ionophore, and Crude Sperm Extract (CSE). Therefore, the aim of this experiment is to know the response use a variety of materials activator of parthenogenetic activation of goat oocytes IVM.The sample used in this experiment was oocytes aspirated from goat ovarian follicles taken from RPH Sukun of Malang. Oocytes were matured for 24 hr in TCM-199 supplemented with fetal bovine serum (FBS), follicle-stimulating hormone (FSH) and lutheinizing hormone (LH) at a temperature of 38,5oC and 5% CO2 in humidified air. After another 30 hours of in vitro maturation, they were then activated by various treatments. The treatment of experiment are treatment 1, activation using ethanol 7% for 7 minute, treament 2, activation using Ca Ionophore 20 µM for 7 minute. Treatment 3, activation using CSE 2,5 µg/ml for 2 hr.Based on the result of research, it is showed that activation by using 7% ethanol for 7 minutes is able to produce cleavage rate of 70.40%. Activation by Ca Ionophore 20 μM for 7 minutes is able to produce cleavage rate of 52.75%. While the use of CSE activation with 2.5 ug / ml for 2 hours produces cleavage rate of 36.33%. Thus it can be concluded that the goat oocyte IVM able to respond to a variety of materials activators on parthenogenetic activation performed. The highest response given by the successive results goat IVM oocytes activated using 7% ethanol for 7 minutes, 20 μM Ca Ionophore for 7 minutes, and the CSE 2.5 microg / ml for 2 hours.Keywords: Parthenogenetic activation, goat oocytes IVM, etanol, calsium ionophore, Crude Sperm Extract (CSE).